The Nation-State Concept in the Crisis of Democracy in Spain - Jiménez Sánchez, José J. (The Age of Human Rights Journal, 2015)
This paper addresses the fundamental reason for the crisis of democracy in Spain, which is closely linked to the most important problem that also faces Europe today. I refer to the consequences of continuing to justify different political practices through the use of the concept of the nation-State. These pages seek rather to analyze that concept to try to explain its ambivalence than to tell the story of its emergence and development. I then propose, through Hegel and especially against Fichte, to establish a new concept, able to avoid the shortcomings of the previous one, which would require us to understand differently the relationship between the two elements, State and nation, which compose it.